The effect of Moringa oleifera L. extract on total cholesterol levels and cardiac hypertrophy in cigarette smoke-exposed mice: An experimental study - Mulyati Sri Rahayu; Sri Wahyuni (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Cigarette smoke contains harmful chemicals that induce oxidative stress by increasing the levels of reactive oxygen species (ROS), thereby complicating cardiovascular disease treatment. Moringa oleifera L., rich in secondary metabolites and antioxidants, has shown medicinal potential. This study aimed to investigate the phytochemical composition of M. oleifera and its potential effects on cardiac hypertrophy and total cholesterol levels in mice exposed to cigarette smoke. Thirty male white mice (Mus musculus) were divided into five groups (n = 6). The negative control group received only food and water, whereas the positive control group was exposed to cigarette smoke without M. oleifera extract. Groups 1, 2, and 3 were exposed to cigarette smoke, and M. oleifera extract was administered at doses of 125, 250, and 500 mg/kg body weight (BW) for 14 days. On the fifteenth day, the mice were sacrificed to obtain heart samples and total cholesterol levels were measured. One-way ANOVA followed by a post-hoc test showed that M. oleifera extract significantly affected cardiac hypertrophy and total cholesterol levels in mice exposed to cigarette smoke (p < 0,05). M. oleifera extract significantly affected cardiac hypertrophy and total cholesterol levels in rats exposed to cigarette smoke with p =0,001 and p=0,000, respectively.